1999
DOI: 10.1034/j.1600-0420.1999.770302.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GABA transporter subtypes (GAT1, GAT3) in the adult rabbit retina

Abstract: ABSTRACT.Purpose: GABA transporters (GATs) are of importance for GABA signal systems. They have previously not been examined in rabbit retina, nor has their correlation with neurotransmitter GABA and GABA receptors been examined in the retina of any species. Methods: The distribution of GATs, GABA and GABA receptors was examined with immunohistochemical methods. Results: Both GAT1 and GAT3 immunoreactivities were found in the inner plexiform layer and in amacrine cells. GAT3 was also present in Müller cells. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Physiological and imaging studies indicate that a GABA plasma membrane transporter may transport GABA both into and out of the cytoplasm of horizontal cells; for example, (1) catfish horizontal cells that contain intracellular GABA, produce an outward current when depolarized (Cammack and Schwartz, 1993), (2) cell lines engineered to express GAT-1 transport GABA into and out of the cell, give an outward current at depolarized potentials that is correlated to the transport of GABA out of the cell (Cammack et al, 1994), and (3) rabbit horizontal cell processes seem to lack significant activity-dependent endocytotic events (Miller et al, 2001). However, the GABA plasma membrane transporters GAT-1, GAT-2, and GAT-3 are not localized to mouse, rat, rabbit, or primate horizontal cells (Brecha and Weigmann, 1994;Johnson et al, 1996;Hu et al, 1999). This finding is consistent with the failure to detect the uptake of GABA or the GABA agonist, muscimol, by mammalian horizontal cells (Pourcho, 1980;Hendrickson et al, 1985;Chun et al, 1988).…”
Section: Vgat Immunoreactivity Is Localized To Horizontal Cellssupporting
confidence: 86%
“…Physiological and imaging studies indicate that a GABA plasma membrane transporter may transport GABA both into and out of the cytoplasm of horizontal cells; for example, (1) catfish horizontal cells that contain intracellular GABA, produce an outward current when depolarized (Cammack and Schwartz, 1993), (2) cell lines engineered to express GAT-1 transport GABA into and out of the cell, give an outward current at depolarized potentials that is correlated to the transport of GABA out of the cell (Cammack et al, 1994), and (3) rabbit horizontal cell processes seem to lack significant activity-dependent endocytotic events (Miller et al, 2001). However, the GABA plasma membrane transporters GAT-1, GAT-2, and GAT-3 are not localized to mouse, rat, rabbit, or primate horizontal cells (Brecha and Weigmann, 1994;Johnson et al, 1996;Hu et al, 1999). This finding is consistent with the failure to detect the uptake of GABA or the GABA agonist, muscimol, by mammalian horizontal cells (Pourcho, 1980;Hendrickson et al, 1985;Chun et al, 1988).…”
Section: Vgat Immunoreactivity Is Localized To Horizontal Cellssupporting
confidence: 86%
“…A relatively weak expression level of GAT-1 was also observed in Mü ller cells of the mouse (Ruiz et al, 1994). In the adult rabbit retina, Mü ller cells express GAT-3 immunoreactivity but apparently no GAT-1 protein (Hu et al, 1999). On the other hand, Mü ller cells of the bullfrog retina express GAT-1 and GAT-2 but not GAT-3 (Zhao et al, 2000), while Mü ller cells from other lower vertebrate species such as the tiger salamander (Yang et al, 1997) and the salmon (Ekström and Anzelius, 1998) apparently do not express GAT proteins.…”
Section: Discussionmentioning
confidence: 95%
“…In the outer retina, for example, the uptake of GABA may be mediated either by Mü ller glial cells (in mammalian species) or by horizontal cells (in nonmammalian species), while in the inner retina of mammals, both Mü ller and amacrine cells are capable of GABA uptake (Marc, 1992). The presence of different GAT proteins has been shown immunohistochemically on Mü ller cells from rat (Brecha and Weigmann, 1994;Honda et al, 1995;Johnson et al, 1996), rabbit (Hu et al, 1999), tiger salamander (Yang et al, 1997), and bullfrog retina (Zhao et al, 2000). However, a detailed electrophysiological characterization of the high-affinity GABA uptake in mammalian Mü ller cells is still missing, and its functional consequences are unknown.…”
Section: Introductionmentioning
confidence: 96%
“…To date, there is no support for a transporter-mediated mechanism in mammalian horizontal cells. For example, GATs have not been localized to rodent and rabbit horizontal cells (Brecha and Weigmann, 1994;Johnson et al, 1996;Hu et al, 1999), and patchclamp recordings of isolated mammalian (rabbit and mouse) horizontal cells have not revealed the presence of GABA-dependent transporter currents (Blanco et al, 1996;Feigenspan and Weiler, 2004). Finally, no highaffinity transport of [ 3 H] GABA or GABA analogs by horizontal cells has been reported for any adult mammalian retina (Ehinger, 1977;Blanks & Roffler-Tarlov, 1982;Mosinger and Yazulla, 1985;Wä ssle & Chun, 1988Löhrke et al, 1994).…”
Section: Transmitter Release From Horizontal Cellsmentioning
confidence: 99%
“…However, GAT isoforms do not localize to horizontal cells in rodent and rabbit retina Weigmann, 1994, Johnson et al, 1996;Hu et al, 1999), and GABA uptake by adult mammalian horizontal cells has not been reported (Ehinger, 1977;Blanks and Roffler-Tarlov, 1982;Mosinger and Yazulla, 1985;Chun, 1988, 1989;Löhrke et al, 1994). Moreover, electrophysiological analyses of GABA-induced currents in isolated horizontal cells from rabbit and mouse retina have not revealed a transporter current (Blanco et al, 1996;Feigenspan and Weiler, 2004).…”
mentioning
confidence: 99%